Strategic Earnings Targeting and Market Discipline in Public Banking: A Qualitative Synthesis of Consumer Pricing and Franchise Value Dynamics - Novrizal; Seger Santoso (LPPM STIE Kasih Bangsa, 2025)
This qualitative literature review explores how strategic earnings targeting in public banking interacts with market discipline, consumer pricing, and franchise value dynamics. By synthesizing findings from recent empirical studies, the paper reveals that earnings management in banks—whether through accrual-based or real activities—is often employed to meet regulatory thresholds and investor expectations, thereby preserving reputational capital and long-term market access. Market discipline both constrains and motivates such behavior, as depositors and investors closely monitor performance signals. The review also highlights how banks strategically set pricing for loans and deposits to align with earnings targets while protecting franchise value amid rising competition and regulatory oversight. Ultimately, the synthesis underscores the complex trade-offs between transparency, performance signaling, and sustainable value creation in the public banking sector